Role for BRG1 in Cell Cycle Control and Tumor Suppression - Hendricks, Kristin B. (Mol Cell Biol, 2004)
Human BRG1, a subunit of the Swi/Snf chromatin remodeling apparatus, has been implicated in regulation of cellular proliferation and is a candidate tumor suppressor. Reintroduction of BRG1 into a breast tumor cell line, ALAB, carrying a defined mutation in the BRG1 gene, induced growth arrest. Gene expression data revealed that the arrest may in part be accounted for by down-regulation of select E2F target genes such as cyclin E, but more dramatically, by up-regulation of mRNAs for the cyclin-dependent kinase inhibitors p21 and p15. Protein levels of both p15 and p21 were induced, and p21 protein was recruited to a complex with cyclin-dependent kinase, CDK2, to inhibit its activity. BRG1 can associate with the p21 promoter in a p53-independent manner, suggesting that the induction of p21 by BRG1 may be direct. Further, using microarray and real-time PCR analysis we identified several novel BRG1-regulated genes. Our work provides further evidence for a role for BRG1 in the regulation of several genes involved in key steps in tumorigenesis and has revealed a potential mechanism for BRG1-induced growth arrest.